(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this article, we introduce a novel structure termed as the non-Archimedean (n, β)-normed space, formulated over a non-Archimedean field. This generalization extends the concept of classical normed spaces by integrating a parameterized framework involving n-tuples and an exponent β. We delve into the fundamental characteristics of these spaces, demonstrating how they connect to standard non-Archimedean n-normed and n-quasi-normed structures. Moreover, we provide examples that support the theory and help show some fixed point results, making these spaces easier to use in real problems.